SOSIALISASI KONSEP PANCASILA DI ERA MODERNITAS BAGI PELAJAR DI SMA NEGERI 16 JAKARTA - Amri, Ibra Fulenzi; Sitabuana, Tundjung Herning; Nethan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
Modernity, as a transformation from pre-modern to modern humanity, coincides with the spread of Western values through globalization, such as individualism, secularism, and materialism, which shape modern human character. This has led to new problems: traditional values have been replaced, and modern humans experience psychological issues due to a loss of meaningful freedom and societal control. This phenomenon also influences the behavior of the